Studies in Malaysian Oral and Musical Traditions - Malm, William P. (Michigan Papers On South And Southeast Asia, 2020)
The first of two studies included is "Music in Kelantan, Malaysia and Some of Its Cultural Implications," by William P. Malm. Kelantan is the northernmost province on the east coast of Malaysia. It is considered to be the most orthodox area in a nation whose state religion is Islam. At the same time it must be noted that it borders to the north with the Buddhist country of Thailand and to the west is the Malaysian province of Perak whose jungles and mountains contain many "pagan" tribal traditions. Beyond Perak is Kedah with its larger Indian and Chinese populations and to the south is Trengganu where some Indonesian traits are still to be found. It is in this context that Malm's study of music is made. The second study is "Professional Malay Story-Telling: Some Questions of Style and Presentation" by Amin Sweeney. In view of the hitherto almost exclusive concern with the content of such tales as those of Sang Kanchil or Pak Pandir, Sweeney throws some light on the form, style, and presentation of oral Malay literature, with special reference to that class of story-telling popularly known as penglipur lara, or what Winstedt termed "folk romances."